The management of direct contracts and its impact on the acquisition of medical implements during the pandemic in the PNP: a case of public corruption - Hinojosa Pérez, José Adolfo (2023)
The objective of this research work is to establish to what extent the management of direct hiring has had an unfavorable impact on the acquisition of medical supplies during the pandemic in the National Police of Peru (PNP). For which the quantitative research method has been applied. The population under study were the officials and servers of the Executing Units of the PNP of Lima and Lambayeque, and the officials of the Comptroller General of the Republic assigned to the Institutional Control Body of the PNP. The results obtained express that direct contracting, being a contracting method, without executing any selection procedure, due to the streamlining and acceleration of formalities, implied that said acts are not carried out respecting the codes of ethics of administrative management, nor have they obtained the best price and quality conditions established by Law No. 30225. Finally, the general conclusion of this research work is that the management of direct contracting has had an unfavorable or negative impact on the acquisition of medical supplies during the pandemic in the PNP.